Molecular and biochemical mechanisms of diabetic encephalopathy - Belenichev, I. F.; Aliyeva, O. H.; Popazova, O. O.; Bukhtiyarova, N. V.; Бєленічев, Ігор Федорович; Алієва, Олена Геннадіївна; Попазова, Олена Олександрівна; Бухтіярова, Ніна Вікторівна (My University, 2023)
Diabetes mellitus is one of the important independent risk factors for the development of neurological disorders such as ischemic stroke, transient ischemic attacks, vascular dementia and neurodegenerative processes. Hyperglycemia plays a crucial role as a trigger in the pathogenesis of these disorders. In this review, we summarize the existing data on the molecular mechanisms of diabetic encephalopathy development, consider the features of oxidative and nitrosative stresses, changes in the thiol-disulfide system, as well as mitochondrial and endothelial dysfunction in diabetes. We focus on the role of HSP 70 in cellular responses in diabetic encephalopathy. HSP70 protein is an important component of the endogenous system of neuroprotection. It acts as an intracellular chaperone, providing the folding, retention, and transport of synthesized proteins, as well as their degradation under both normoxic and stress-induced denaturation conditions. HSP70 can be considered a molecular marker and a promising therapeutic target in the treatment of diabetes mellitus.
Keywords: diabetes mellitus; diabetic encephalopathy; thiol-disulfide system; mitochondrial dysfunction; HSP70; HIF-1a